QUALITY OF AMOXICILLIN TRIHYDRATE/POTASSIUM CLAVULANATE TABLETS COMMERCIALLY AVAILABLE IN LIBYAN PHARMACEUTICAL MARKET - EL-HDDAD, SANADELASLAM; SULIMAN, MOHAMMED B. (International Journal of Applied Pharmaceutics, 2023)
Objective: The objective of this study was to compare the quality of the amoxicillin trihydrate/potassium clavulantae (co-clavimox) tablets those are locally available in Libyan pharmaceutical market manufactured by various pharmaceutical companies with United State Pharmacopeia (USP) standards. Methods: The five popular brands (clavomid, augmentin, clavodar, clamoxin, and clavimox) of co-clavimox conventional tablet of 625 mg strength were chosen. The quality of commercial products was evaluated through the identification of the content of active pharmaceutical ingredients (APIs) using UV- Spectrophotometer. Results: The results obtained showed that, the products clavomid, augmentin, and clavodar conformed to the USP standard limit for quantitative assay of active ingredients. Clamoxin passed the standard limit test with a slight deviation (<2%), while clavimox failed the test with values far below the acceptable range. Conclusion: This study has been able to confirm that some generic brands of co-clavimox tablets available in the Libyan markets possess qualities below official recommendations. Therefore, there is an urgent need for constant monitoring of different brands of medications in the market to ensure their safety and quality.